2015
DOI: 10.1038/hgv.2015.24
|View full text |Cite|
|
Sign up to set email alerts
|

Novel rare variations of the oxytocin receptor (OXTR) gene in autism spectrum disorder individuals

Abstract: The oxytocin receptor (OXTR) gene has been implicated as a risk gene for autism spectrum disorder (ASD)-a neurodevelopmental disorder with essential features of impairments in social communication and reciprocal interaction. The genetic associations between common variations in OXTR and ASD have been reported in multiple ethnic populations. However, little is known about the distribution of rare variations within OXTR in ASD patients. In this study, we resequenced the full length of OXTR in 105 ASD individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Only one SNP overlapped with strong signatures of transcriptional function, a SNP occurring at nucleotide 213739 (NT213739, minor allele frequency: 0.32) (Figure 3b). The sequence containing NT213739 overlapped peaks of DNase hypersensitivity and CTCF binding within the large intron, a region proposed to contain cis -REs in humans (20, 61, 62). Based on this evidence we chose to further investigate the predictive power of NT213739 in two additional samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one SNP overlapped with strong signatures of transcriptional function, a SNP occurring at nucleotide 213739 (NT213739, minor allele frequency: 0.32) (Figure 3b). The sequence containing NT213739 overlapped peaks of DNase hypersensitivity and CTCF binding within the large intron, a region proposed to contain cis -REs in humans (20, 61, 62). Based on this evidence we chose to further investigate the predictive power of NT213739 in two additional samples.…”
Section: Resultsmentioning
confidence: 99%
“…In the human OXTR third intron, the CTCF peak is found near a SNP, rs237887, that was predicted to be near a cis -RE, and associated with face recognition abilities (20) and ASD diagnosis (21). Additionally, the human intron may contain other cis -REs (61) and accumulates rare SNPs in cases of ASD (62). If the large intron of Oxtr contains cis -REs in multiple species, spatial organization of DNA by factors such as CTCF could offer a potentially general regulatory mechanism required for proper function of species or region-specific cis -REs.…”
Section: Discussionmentioning
confidence: 99%
“…A variant in R150, R150S, was previously identified in an individual with autism spectrum disorder 24 . This residue is part of the oxytocin receptor ‘polar pocket’, which changes conformation during receptor activation and is involved in G-protein interaction 2527 .…”
Section: Commentmentioning
confidence: 99%
“…Genetic studies also suggested a role of OXT in ASD. The region of chromosome 3, in which OXTR is located is now considered a susceptibility locus, as it has repeatedly been found to be implicated in ASD (Liu et al, 2016;Jansen et al, 2006;Ebstein et al, 2009;Andari et al, 2010;Green et al, 2001;Guastella et al, 2010;Wang and Hatton, 2009;Sala et al, 2011;Schmidt et al, 2012;Guastella et al, 2008;Kurth et al, 2011). Wu et al have reported an association between two single nucleotide polymorphisms (SNP) in the OXTR related to the occurrence of ASD (Wu et al, 2005).…”
Section: Genetic Studiesmentioning
confidence: 99%